Flow of a micropolar fluid on a continuous moving surface (Archives of Mechanics - Test, 2006)
The present paper deals with the analysis of steady boundary layer flow and heat transfer of a micropolar fluid on an isothermal continuously moving plane surface. It is assumed that the microinertia density is variable and not constant, as in many other published papers. Also, the viscous dissipation effect is taken into account. The basic partial differential equations are reduced to a system of nonlinear ordinary differential equations, which is solved numerically using the Keller-box method. Numerical results are obtained for the skin friction coefficient, local Nusselt number, as well as velocity, temperature and microrotation profiles. Results are shown in graphical form and the numerical values for the skin friction coefficient and local Nusselt number are given in the form of tables. The effects of material parameter K, Prandtl number Pr and Eckert number Ec on the flow and heat transfer characteristics are discussed.